ANALISIS ETIKA PROFESI GURU PAUD DALAM MENDUKUNG PERKEMBANGAN NILAI AGAMA, MORAL, DAN SOSIAL EMOSIONAL ANAK - Dwi Yasminasari; Asya Ilfana; Umniyah Zahroh; Muhlisin Muhlisin; Abul Mafaakhir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of teacher professional ethics in implementing a love-based curriculum to support the development of religious, moral, and socioemotional values in early childhood. This research uses a qualitative approach with a literature study method by reviewing various relevant scientific sources such as journals, books, and proceedings. The results show that a love-based curriculum emphasizes affection, empathy, and positive relationships between teachers and children, which significantly contribute to children's character development. Teacher professional ethics, including responsibility, fairness, and exemplary behavior, plays a crucial role in creating a supportive learning environment. Furthermore, the integration of a love-based curriculum effectively enhances children's moral awareness and socio-emotional skills. Therefore, the synergy between teacher ethics and a love-based curriculum is essential in achieving holistic early childhood education.